Local analgesia for neonatal circumcision - Stellwagen, Lisa; Wang, Marvin; Acker, David; Partners HealthCare ([Elk Grove Village, Ill.] : American Academy of Pediatrics, 1999)
(Producer) This pediatric training video, developed by Lisa Stellwagen, MD, Marvin Wang, MD, and Massachusetts General Hospital, demonstrates a neonatal circumcision using dorsal penile nerve block and both references and supports the 1999 AAP circumcision policy statement
Videocassette is available at Koleksi Media, Perpustakaan HUKM
Lisa Stellwagen, Marvin Wang, David Acker
Keywords: Circumcision -- methods -- infant, newborn; Anesthesia, Local -- methods -- infant, newborn; Lidocaine -- therapeutic use -- infant, newborn